(untitled) (Journal of Engineering Science, 2023)
The equality of gender is accounted to be an indispensable element when it comes to sustainable transportation infrastructure planning in an inclusive society. Special attention in this regard must be required to reach the growing transportation demands of the urban population- especially in a developing country like Bangladesh. In this inclusive society, females constitute a major portion of the students as well as the workforce and contribute significantly to the economy. Although females have to rely on the different modes available in the existing transportation system for their day-to-day travel, they have different preferences among the alternative modes in terms of accessibility and safety. To assess the travel behavior of female students, this study explores the elements those influence travel choices (travel cost, travel time, security, and comfort) and evaluates the effect of ride-sharing facilities on their choice of mode. Data were collected from 360 female university students through an online questionnaire. The research focuses on two divisions of female students: staying at the residence hall (residents) and not staying at the residence hall (non-residents). Descriptive and inferential statistical methods were utilized to explain female travel behaviors and determine the importance of ridesharing services in their mode selection (rickshaw, bus, autorickshaw, bicycle, private car, and ridesharing). The study reveals that female students (both resident and non-resident) prefer rickshaws over other modes and the inception of ride-sharing services had a consequential effect on their choice of modes and travel behavior. This analysis will deliver beneficial information to relevant authorities and policymakers in evaluating existing transportation systems and will indicate the required mitigations that can be made to ensure social equity. Journal of Engineering Science 13(2), 2022, 43-49